1985
DOI: 10.1136/hrt.53.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease and haemostatic variables in heterozygous familial hypercholesterolaemia.

Abstract: SUMMARY Haemostatic variables were measured in 61 patients with heterozygous familial hypercholesterolaemia, 32 of whom had evidence of coronary heart disease. Age adjusted mean concentrations of plasma fibrinogen and factor VIII were significantly higher in these patients than in the 29 patients without coronary heart disease, but there were no significant differences in serum lipid concentrations between the two groups. Comparisons in 30 patients taking and not taking lipid lowering drugs showed lower values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…An earlier comparison of FH cases with and without CHD [16] found no significant differences in levels of plasma cholesterol and TG; however, levels of fibrinogen and coagulation factor VIII were significantly higher in the group with CHD. Among heterologous FH cases, high plasma lipid levels were not associated with CHD but hypercoagulability was a likely cause of CHD pathogenesis (Fig.…”
Section: Critical Interpretation Of the Statement Based On Mendelian mentioning
confidence: 99%
See 3 more Smart Citations
“…An earlier comparison of FH cases with and without CHD [16] found no significant differences in levels of plasma cholesterol and TG; however, levels of fibrinogen and coagulation factor VIII were significantly higher in the group with CHD. Among heterologous FH cases, high plasma lipid levels were not associated with CHD but hypercoagulability was a likely cause of CHD pathogenesis (Fig.…”
Section: Critical Interpretation Of the Statement Based On Mendelian mentioning
confidence: 99%
“…Data based on Surgrue et al [16]. CHD was associated with significantly increased levels of fibrinogen and coagulation factor VIII but not with increased levels of classical risk factors such as LDL-C, HDL-C, and TG.…”
Section: Critical Interpretation Of the Statement Based On Mendelian mentioning
confidence: 99%
See 2 more Smart Citations
“…Coagulation factors, specifically fibrinogen and factor VII, (serum prothrombin conversion accelerator) have been implicated as risk factors for atherosclerotic diseases (Wilhelmsen et al, 1984;Meade et al, 1986). Several cross-sectional studies also have suggested an association between factor VIII and von Willebrand factor (vWF) with atherosclerotic heart disease, but other studies have found no association with heart disease (Sugrue et al, 1985;Myreng et al, 1986). Thus, a reduction in the risk of CAD can be related to the prevention of clotting or thrombosis, especially because 90% of patients with fatal myocardial infarction have associated coronary thrombosis.…”
Section: Introductionmentioning
confidence: 99%